LOS PREMIOS DARWIN: LA CIENCIA DE LO ABSURDO - Balarezo-López, Gunther (2019)
The Darwin Awards are awarded posthumously to people who have performed a stupid act and have lost their lives as a result of that act, so part of the assumption that the human being less endowed genetically, does not survive. To do this, a bibliographical review was made on the internet (academic google and descriptor DeCS), because no information was found in other sources. This award has aroused the curiosity of researchers to explain the reasons why men expose themselves more than women to dangerous situations, even postulating the “male idiocy theory”.